Identification of factors influencing refusal COVID-19 vaccine using FAHP / Norpah Mahat, Nur Izyan Nabilah Mohd Zain and Izleen Ibrahim - Mahat, Norpah; Mohd Zain, Nur Izyan Nabilah; Ibrahim, Izleen (Universiti Teknologi MARA Press (Penerbit UiTM), 2023)
The pandemic Coronavirus (COVID-19) has spread rapidly worldwide, initially emerging in China. It had spread to more than 180 nations and infected more than 18.4 million people just over six months as recorded in August 2020. Thus, all countries were fighting to get rid of this virus and to find a vaccine. The COVID-19 vaccine is currently being offered to people who qualify, but many Malaysians chose not to sign up to receive the immunization. The initial booster dose of vaccine was only administered to half of the nation's total population. Studying the motivational elements and health beliefs that influence vaccination decisions is necessary. Therefore, the objective of this study is to identify the factors that influence the refusal of the Covid-19 vaccine. The Statistical Package for the Social Sciences (SPSS) will be used to assess the correlation analysis of the variables impacting COVID-19 vaccine rejection. As part of the investigation, the Fuzzy Analytics Hierarchy Process (FAHP) will be used to investigate associated factors. Considered were seven variables that affect vaccine refusal. The finding showed the perception of vaccine safety, and its effectiveness factor is the highest correlation that influences the refusal of the vaccine. It is followed by social factors, the rumours spread by the media, education level, previous experience, knowledge, and public health policies. Furthermore, the result from the FAHP method shows that previous experience is the top-rank factor influencing the refusal of the COVID-19 vaccine since it has a high weight value. The second rank is knowledge, followed by education, public health policies, social, perception of vaccines, and the rumour spread by media. This research contributes to the understanding of the factors influencing Covid-19 vaccine refusal in Malaysia and provides possible targeted vaccination campaigns that are appropriate and effective towards increasing population immunity.